High-Order Local Absorbing Boundary Conditions for Heat Equation in Unbounded Domains (Journal of Computational Mathematics, 2018)
With the development of numerical methods the numerical computations require higher and higher accuracy. This paper is devoted to the high-order local absorbing boundary conditions (ABCs) for heat equation. We proved that the coupled system yields a stable problem between the obtained high-order local ABCs and the partial differential equation in the computational domain. This method has been used widely in wave propagation models only recently. We extend the spirit of the methodology to parabolic ones, which will become a basis to design the local ABCs for a class of nonlinear PDEs. Some numerical tests show that the new treatment is very efficient and tractable.
Keywords: Heat equation; High-order method; Absorbing boundary conditions; Parabolic problems in unbounded domains.